2015
DOI: 10.1158/2159-8290.cd-14-0595
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Colorectal Cancer Invasion and Metastasis through Activation of NOTCH–DAB1–ABL–RHOGEF Protein TRIO

Abstract: We have recently identifi ed a metastasis suppressor gene for colorectal cancer: AES / Aes , which encodes an endogenous inhibitor of NOTCH signaling. When Aes is knocked out in the adenomatous epithelium of intestinal polyposis mice, their tumors become malignant, showing marked submucosal invasion and intravasation. Here, we show that one of the genes induced by NOTCH signaling in colorectal cancer is DAB1 / Dab1 . Genetic depletion of DAB1 suppresses cancer invasion and metastasis in the NOTCH signaling-act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 56 publications
(55 reference statements)
2
89
0
Order By: Relevance
“…Together, these interactions allow the Abl signaling network to control a wide variety of axon patterning decisions throughout animal phylogeny, perhaps by coordinating the Ena-dependent dynamics of linear actin bundles with the WAVE-dependent dynamics of branched actin networks. The relationship of Dab to Abl has long been controversial (Gertler et al, 1993;Howell et al, 1997;Liebl et al, 2003;Song et al, 2010;Sonoshita et al, 2015). For some time, it was unclear whether Dab is even a core component of the Abl pathway, although more recently we established the central role of Dab in Abl pathway function (Liebl et al, 2003;Song et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these interactions allow the Abl signaling network to control a wide variety of axon patterning decisions throughout animal phylogeny, perhaps by coordinating the Ena-dependent dynamics of linear actin bundles with the WAVE-dependent dynamics of branched actin networks. The relationship of Dab to Abl has long been controversial (Gertler et al, 1993;Howell et al, 1997;Liebl et al, 2003;Song et al, 2010;Sonoshita et al, 2015). For some time, it was unclear whether Dab is even a core component of the Abl pathway, although more recently we established the central role of Dab in Abl pathway function (Liebl et al, 2003;Song et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2A,B It has been suggested that the Abl and Dab orthologs associate in mammalian cells (Sonoshita et al, 2015). We therefore tested Abl/ Dab association in Drosophila by co-immunoprecipitation (co-IP) from embryo extracts and found that immunoprecipitation of Abl co-precipitated Dab (Fig.…”
Section: Dab Regulates Abl Kinase Activitymentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, Abl kinases promote the expression and/or localization of other proteins that regulate cell invasion, such as the type 1-matrix metalloproteinase MT1-MMP (also known as MMP14) (Chevalier et al, 2015;Mader et al, 2011;Smith-Pearson et al, 2010). A recent report demonstrated a so-far-unknown role for Abl kinases in promoting the invasion and metastasis of colorectal cancer cells, by linking the activation of NOTCH to the phosphorylation of TRIO, which enhances its Rho-GEF activity, leading to a corresponding increase of Rho-GTP levels (Sonoshita et al, 2015) (see poster).…”
Section: Role For Abl Kinases In Solid Tumorsmentioning
confidence: 99%
“…Indeed, in mammalian cells it is known that Abl and Src phosphorylate tyrosine residues in the C-terminal portion of Trio to stimulate its Rho GEF activity. 40 The Trio domain that is phosphorylated in that model, however, is not conserved in the fly protein, ruling it out as the mechanism of Rac GEF activation in our experiments. Previous studies showed in vitro binding of purified Drosophila Abl and Trio fragments from cells, and overexpression of Abl was capable of increasing Trio phosphorylation.…”
Section: Introductionmentioning
confidence: 70%